Isolation and Molecular Phylogenetic Characterization of Cadmium-Tolerant Hydrocarbon Degrading Bacteria - Chew, Efendy (2016)
Three bacteria isolates (A, B and C) previously shown to biodegrade hydrocarbons were subjected to cadmium (Cd) toxicity test at 0.1 mg/L and 1.0 mg/L. of the three isolates, only two (isolates A and C) were observed to survive Cd at the two tested concentration. Increasing the Cd concentration 10 times higher from 0.1 mg/L to 1.0 mg/L did not inhibit the growth of both isolates (p>0.05). However isolate C showed the highest growth (p<0.05) at the highest concentration of Cd tested at 1.0mg/L, which is 100 times higher than the permissible limit for Cd in industrial effluent according to the Malaysian Environmental Quality Regulations. Gram staining results showed that isolate C to be Gram negative. DNA was successfully extracted from isolate C, visualized as a single band on 1.2% agarose gel. Amplification of the DNA extracted using primers targeting the 16s rDNA region yielded a band size of 1500bp. The PCR product was sequenced and the sequence obtained was used successfully to construct a phylogenetic tree, identifying the Cd resistant bacteria to be Pseudomonas aeruginosa.